Moral consequences of becoming unemployed - Barr, Abigail; Miller, Luis; Ubeda, Paloma (National Academy of Sciences, 2016)
We test the conjecture that becoming unemployed erodes the extent to which a person acknowledges earned entitlement. We use behavioral experiments to generate incentive compatible measures of individuals’ tendencies to acknowledge earned entitlement and incorporate these experiments in a two-stage study. In the first stage, participants’ acknowledgement of earned entitlement was measured by engaging them in the behavioral experiments and their individual employment status and other relevant socio-economic characteristics were recorded. In the second stage, a year later, the process was repeated using the same instruments. The combination of the experimentally generated data and the longitudinal design allows us to investigate our conjecture using a difference-in-difference approach, while ruling out the pure self-interest confound. We report evidence consistent with a large, negative effect of becoming unemployed on the acknowledgement of earned entitlement.